Abstracts 2018
DOI: 10.1136/injuryprevention-2018-safety.226
|View full text |Cite
|
Sign up to set email alerts
|

PW 2206 The relationship between smoking habits and unsafe behaviour on the roads

Abstract: From the review of literature it is widely accepted that the use of a seat belt reduces the risk of death in road traffic by up to 65% and the use of reflectors reduces pedestrian accidents and death by 75%–85%. Careless behaviour on roads can increase the risk of a crash and serious injury. As smoking has been linked to risky behaviour, the aim of the study was to examine the relationship between self-reported smoking and road safety behaviour in Latvia.MethodsThe data of ‘Health behaviour among the Latvian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Surprisingly, smokers were more likely to report seatbelt use. This finding is contrary to what has been reported previously (29). Moreover, a study conducted in Kuwait showed that smokers were less likely to buckle up and more likely to be involved in road traffic accidents (31).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Surprisingly, smokers were more likely to report seatbelt use. This finding is contrary to what has been reported previously (29). Moreover, a study conducted in Kuwait showed that smokers were less likely to buckle up and more likely to be involved in road traffic accidents (31).…”
Section: Discussioncontrasting
confidence: 83%
“…Similar results were found in a study that examined risk behavior among teens with chronic conditions, such as cystic fibrosis and sickle cell disease. The study concluded that ill teenagers were more likely to fasten their seatbelts than their healthy counterparts (29). In the same manner, the higher compliance rate among survey participants who brush their teeth more than others may be explained by the possibility that they have adopted a healthier lifestyle.…”
Section: Discussionmentioning
confidence: 91%